Traumatic Events, Social Adversity and Discrimination as Risk Factors for Psychosis - An Umbrella Review - Varchmin, Leonie; Montag, Christiane; Treusch, Yvonne; Kaminski, Jakob; Heinz, Andreas (Frontiers in Psychiatry, 2021)
Exposure to childhood trauma is a well-known risk factor for severe mental disorders including schizophrenia and other non-affective psychoses. Beyond childhood trauma, there is increasing evidence that bullying, social exclusion and discrimination during adolescence and adulthood may increase the risk to develop a psychotic disorder, and that such forms of traumatization may also underlie the elevated psychosis risk among migrants or persons with a visible minority status. In this umbrella review, we systematically assess meta-analyses regarding trauma and social adversity. A systematic literature review yielded 11 meta-analyses that met inclusion criteria and could be summarized quantitatively with a random effect model. Further six meta-analyses were evaluated qualitatively. Heterogeneity and publication bias were apparent in several meta-analysis. We observed that most significant social risk factors for psychosis were vulnerability for racist discrimination (OR = 3.90 (3.25-4.70)), migration (OR =2.22 (1.75 – 2.80)) and childhood adversities (OR = 2.81 (2.03 -3.83)). Further social factors increasing the risk for psychosis were variation/impairment of parental communication, aversive adult life events, bullying and factors associated with social isolation and discrimination. In spite of these environmental risk factors, there is a lack of evidence regarding treatment of trauma and psychosis, although some psychotherapeutic and art therapy approaches appear to be promising. Beyond individual interventions, stigmatization, racism and other forms of discrimination need to be targeted to increase solidarity and communal support.